Oral care in cancer nursing: Practice and barriers - Radhika R Pai; Ravikiran Ongole; Sourjya Banerjee (Wolters Kluwer Medknow Publications, 2019)
Background: Oral health awareness and oral care are crucial aspects of oncology nursing practice. However, very few studies concentrate on the oral care of cancer patients undergoing cancer treatment and nursing practice in the Indian subcontinent scenario/situation. Most of the published studies have been conducted in the Western and European countries. Aims: This study aimed to determine the nurses' practice and barriers regarding oral care in cancer patients undergoing chemotherapy and radiation therapy. Materials and Methods: A cross-sectional descriptive survey was conducted among 158 staff nurses working in oncology-related areas from four different hospitals of Dakshina Kannada district and Udupi district of Karnataka state, India. Statistical Analysis: Descriptive and inferential statistics was used by using SPSS 16 version. Results: More than half of respondents [54 (34.2%)] did not perform oral care as a part of routine duties. Maintenance of various records, lack of manpower, and lack of standard operating procedures were major barriers in providing oral care. Documentation audit revealed that nurses recorded oral care in the chart only when order was present in the care sheet, but oral problem assessment was not recorded at all. In all four hospitals surveyed, there was no protocol specifically designed for oral care of cancer patients. Conclusion: Nurses expressed that oral care in cancer patients was one of the most ignored aspect in oncology nursing. Our result highlights the need to develop evidence-based oral care intervention protocol and motivate staff nurses to attend continuing nursing educations regularly to keep themselves abreast of the latest trends in order to render comprehensive care to the patients.